2022
DOI: 10.1186/s13071-022-05462-w
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of Simulium damnosum sensu lato breeding sites and species distribution in Sudan savanna, mixed savanna–forest and rainforest regions in Cameroon

Abstract: Background The presence of breeding sites and distribution of species of Simulium damnosum sensu lato are critical in understanding the epidemiology of onchocerciasis and evaluating the impact of elimination interventions. Reports on breeding sites and species distribution of members of S. damnosum s.l. in Cameroon are scarce and the few ones available date back to more than three decades. The aim of this study is to provide information on S. damnosum breeding sites across the rainy (RS) and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…This study has shown that black y vectors are still abundant in this area, with de nite seasonality in their human biting activities in the study area. Similar to previous observations [17], black ies biting in the dry season are exclusively concentrated around the major perennial rivers while in rainy season they mostly occur in the seasonal tributaries of these rivers. Hence, we recommend taking this information into consideration when planning for vector surveillance in the region, as well as when scheduling CDTI (as treatment is recommended to be done during peak transmission, which is generally assumed to coincide with peak y densities).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study has shown that black y vectors are still abundant in this area, with de nite seasonality in their human biting activities in the study area. Similar to previous observations [17], black ies biting in the dry season are exclusively concentrated around the major perennial rivers while in rainy season they mostly occur in the seasonal tributaries of these rivers. Hence, we recommend taking this information into consideration when planning for vector surveillance in the region, as well as when scheduling CDTI (as treatment is recommended to be done during peak transmission, which is generally assumed to coincide with peak y densities).…”
Section: Discussionsupporting
confidence: 90%
“…Many seasonal rivers (locally called Mayo) criss-cross the study area, some of which support black ies breeding when owing in the rainy season. The main reported vector cytospecies at the different sites are S. damnosum s.s. and small proportion of S. sirbanum, and often with seasonal occurrence of small numbers of S. mengense and S. squamosum (17,19).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…S. damnosum sensu stricto and S. sirbanum were the main species in the north, whereas S. squamosum and S. mengense were the predominant species in the north west and south west. Simulium soubrense and S. yahense were uniquely recorded in the south west[42]. Studying the Onchocerca ochengi transmission dynamics and the correlation of O. ochengi microfilaria density in cattle with transmission potential, Achukwi et al[43] observed a high biting rate of Simulium s.l.…”
mentioning
confidence: 99%